2019
DOI: 10.1186/s40359-019-0310-3
|View full text |Cite
|
Sign up to set email alerts
|

Offering mental health first aid to a person with depression: a Delphi study to re-develop the guidelines published in 2008

Abstract: Background Depressive disorder is ranked as the largest contributor to non-fatal health burden. However, with prompt treatment, outcomes can improve. Family and friends are well placed to recognise the signs of depression and encourage early help seeking. Guidelines about how members of the public can provide mental health first aid to someone who is experiencing depression were developed in 2008. A Delphi study was conducted to re-develop these guidelines to ensure they are current and reflect be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 16 publications
(11 reference statements)
1
44
1
1
Order By: Relevance
“…However, the correlation coefficient observed in this study is much smaller compared to those reported in similar studies in English-speaking countries. For example, Bond et al reported a correlation coefficient of 0.95 between panels of professionals and consumers in a Delphi study to re-develop the mental health first aid guidelines for depression [26]. Such difference is likely to be due to the truncated range, as the statements with low endorsement in the English-language questionnaire were not included in the Chinese questionnaire.…”
Section: Comparison Of Ratings Between the Two Panelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correlation coefficient observed in this study is much smaller compared to those reported in similar studies in English-speaking countries. For example, Bond et al reported a correlation coefficient of 0.95 between panels of professionals and consumers in a Delphi study to re-develop the mental health first aid guidelines for depression [26]. Such difference is likely to be due to the truncated range, as the statements with low endorsement in the English-language questionnaire were not included in the Chinese questionnaire.…”
Section: Comparison Of Ratings Between the Two Panelsmentioning
confidence: 99%
“…There are many methods that may be used as part of a cultural adaptation process for behavioural health interventions [48]. The Delphi method offers a systematic way of doing this and is particularly appropriate for this study, because it parallels the process used to inform the English-language guidelines [26]. There is now a need for further exploration of how the adapted guidelines, and the associated training, might be implemented in the Chinese context, in consideration of its mental health care system, existing workforce and cultural values.…”
Section: Considerations For Future Use Of the Adapted Guidelinesmentioning
confidence: 99%
“…By using this method to develop an evidence base to guide decisions, policymakers and practitioners can move beyond relying on their own experience and draw on the accumulated experience of a larger, expert group [41]. This method has been widely used in disparate fields [41], including in mental health research, for example in the development of mental health first aid guidelines for English-speaking countries and some LMICs [30,32,34,42].…”
Section: The Delphi Methodsmentioning
confidence: 99%
“…The content of the current MHFA training course is based on guidelines for how members of the public might help people with a wide range of mental health problems (e.g. psychosis, depression or trauma) [29][30][31] and crises (e.g. suicide) [32].…”
mentioning
confidence: 99%
See 1 more Smart Citation